2015
DOI: 10.1108/ijpsm-03-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio management of development projects in Danish municipalities

Abstract: Purpose – Danish municipalities are undergoing continuous changes. An important part of these changes are the introduction and implementation of a wide range of development projects. The purpose of this paper is to focus on the challenges of initiation and implementation of development projects in municipalities. Design/methodology/approach – The focus is on development projects, which are defined as projects undertaken to improve the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Ethnic tensions negatively affect public sector employee motivation and job performance. This argument is parallel to the findings of the studies conducted by Cheng (2015), Arlbjørn et al (2015), and Ababneh (2016). These studies also found that the political environment affects public sector motivation and job performance.…”
Section: Research Findingssupporting
confidence: 70%
See 1 more Smart Citation
“…Ethnic tensions negatively affect public sector employee motivation and job performance. This argument is parallel to the findings of the studies conducted by Cheng (2015), Arlbjørn et al (2015), and Ababneh (2016). These studies also found that the political environment affects public sector motivation and job performance.…”
Section: Research Findingssupporting
confidence: 70%
“…The second variable is the "technological environment" that has an impact on human resource activities. The third variable is the "political environment" that affects employee's morale, motivation, and job performance (Schuler et al 1993;Dowling 1999;Brewster 1999;Boyne et al 1999;Cheng 2015;Arlbjørn et al 2015;Ababneh 2016). Another variable is the "sociocultural environment" that includes societal values, norms, beliefs, customs, and work ethics that affect the management of human resources (Schuler et al 1993;Dowling 1999;Kalpazidou 2008;Cannaerts et al 2016;Ohemeng 2010).…”
Section: Contingency Theorymentioning
confidence: 99%
“…As posited before, the managerial focus on policy networks and its link to organizational ambidexterity remain understudied (Smith and Umans, 2015; Palm and Lilja, 2017). To overcome this limitation and apply traditional management concepts from the private sector to public sector effectively (Stentoft Arlbjørn et al , 2015, p. 14). We propose the use of case studies to understand the complexity of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, managerial focus on policy networks and its link to organizational ambidexterity thus remain understudied (Smith and Umans, 2015; Palm and Lilja, 2017). As Stentoft Arlbjørn et al (2015, p. 14) note: “They are so different that it is problematic to transfer management tools from the private sector to public sector without further reflection”. (Therefore, the motivation of this paper is to contribute to previous literature by understanding which factors support ambidexterity in policy networks to foster SMEs innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Juga ada teori set lunak dan model hierarkis analitik di bawah kesederhanaan digabungkan. Keuntungan utama dari metode ini dibandingkan dengan yang lain adalah metode hibrida sangat sederhana dalam hal perhitungan dan kompleksitas komputasi dari algoritma yang diusulkan rendah [33].…”
Section: Metode Keputusan Multi Kriteriaunclassified